2017
DOI: 10.1103/physrevb.95.245210
|View full text |Cite
|
Sign up to set email alerts
|

Electron-phonon scattering from Green's function transport combined with molecular dynamics: Applications to mobility predictions

Abstract: We present a conceptually simple method for treating electron-phonon scattering and phonon limited mobilities. By combining Green's function based transport calculations and molecular dynamics (MD), we obtain a temperature dependent transmission from which we evaluate the mobility. We validate our approach by comparing to mobilities and conductivies obtained by the Boltzmann transport equation (BTE) for different bulk and one-dimensional systems. For bulk silicon and gold we successfully compare against experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…In Ref. 146 we showed that the average transmission from a thermal distribution of configurations accurately describes the inelastic electron transmission spectrum due to electron-phonon scattering at this temperature. In the special thermal displacement (STD) method, the average is replaced with a single representative configuration, which may drastically reduce the computational cost of inelastic transport simulations.…”
Section: Special Thermal Displacement Methodsmentioning
confidence: 95%
“…In Ref. 146 we showed that the average transmission from a thermal distribution of configurations accurately describes the inelastic electron transmission spectrum due to electron-phonon scattering at this temperature. In the special thermal displacement (STD) method, the average is replaced with a single representative configuration, which may drastically reduce the computational cost of inelastic transport simulations.…”
Section: Special Thermal Displacement Methodsmentioning
confidence: 95%
“…Correspondingly, electron transport is calculated for configurations with fixed atomic positions which are, however, displaced from the equilibrium lattice sites to simulate the temperature induced atomic vibrations. One direct approach to create an appropriate set of atomic displacements is to superpose all allowed modes and generate one corresponding configuration [52,53], while another approach employs repeated calculations over an ensemble of systems in order to account for thermodynamic fluctuations [38], where each system exhibits different random displacements which are determined by molecular dynamics [38] or a chosen spatial distribution function [37,54]. In this work, we displace both bulk and surface atoms in the scattering region from their equilibrium position by a vector Δ, which is randomly determined for each atom by independently choosing its x, y, and z-coordinates from a uniform distribution…”
Section: Computational Proceduresmentioning
confidence: 99%
“…First-principles simulations that explicitly account for the atomic level structure and associated electronic structure of the thin film are expected to yield correct transport data for very thin films and nanowires [15,21,[36][37][38][39][40][41][42]. They do not directly provide a functional form for ρ as a function of, for example, layer thickness, surface roughness, bulk (phonon) scattering or metal element.…”
Section: Introductionmentioning
confidence: 99%
“…33. Such DFT calculation of the resistivity of metals is computationally demanding as one needs to integrate the electron-phonon coupling over both electron and phonon wave vectors (k-and q-space, respectively), and only few studies of the electron-phonon coupling in metals exist that includes a full integration [8,25,36,37]. For the integration of the scattering rate we use a sampling of 30×30×30 q-points and tetrahedron integration.…”
Section: Bulk Characteristicsmentioning
confidence: 99%